Glucoamylase Production by Aspergillus awamori KT-11 In Solid State Fermentation Using Cassava Peel as Substrate - Urip Perwitasari; Nuryati Nuryati; Ruth Melliawati; Yopi Yopi (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2017)
In order to utilization of cassava peel waste this study tries to produce glucoamylase by solid state fermentation with Aspergillus awamori KT-11. Composition medium and drying technique are affecting the glucoamylase production. The highest glucoamylase activities were from cassava peel plus mineral medium. Activity glucomaylase in cassava peel plus mineral medium by oven drying was 365 U/mL and freeze dring was 452 U/mL. It is conclud cassava peel plus mineral is a better substrate for glucoamylase production from A. awamori KT-11 in solid state fermentation. Powder of glucoamylase also proved capable of hydrolyzing starch-based biomass.